Viable pregnancies beyond 28 weeks gestation in women with a history of unexplained recurrent miscarriage have reduced platelet function. (May 2016) - Dempsey, Mark A.; Flood, Karen; Burke, Naomi; Murray, Aoife; Cotter, Brian; Muellers, Siglinde; Dicker, Patrick; Fletcher, Patricia; Geary, Michael; Malone, Fergal D.; Kenny, Dermot
Abstract: Objective: The aim of this study was to characterize platelet function in pregnant patients with a history of unexplained recurrent miscarriage (RM) in the third trimester of a subsequent viable pregnancy, a time at which platelet dysfunction may be associated with an increased obstetric risk. Study design: A prospective study was performed comparing 30 viable pregnancies that had reached at least 28 weeks' gestation amongst patients who had a background history of unexplained RM, with 30 healthy pregnant controls at a similar gestational age. Platelet function was determined by means of platelet aggregation in response to 5 different agonists at multiple concentrations. Results: Amongst the 30 RM patients with ongoing viable pregnancies, we demonstrated significantly reduced platelet aggregation compared to the pregnant controls in the third trimester. For three out of five agonists, we demonstrated statistically significantly decreased platelet aggregation and for all five agonists we demonstrated significantly decreased platelet aggregation in the postnatal period. There were no obvious differences in obstetric outcomes. Conclusion: This study shows that women with a history of unexplained RM have reduced platelet function after 28 weeks' gestation in their subsequent pregnancies compared to healthy pregnant controls, but without this difference leading to any obvious increase in adverse obstetric risk.